SYSTEMIC HEMOSTATIC AND PROTHROMBOTIC EFFECTS OF FIBRIN-MONOMER IN EXPERIMENT WITH DOSED LIVER THERAPY - A. P. Momot; V. M. Vdovin; I. I. Shakhmatov; I. G. Tolstokorov; D. A. Orekhov; V. O. Shevchenko; N. A. Lycheva; A. V. Kudinov; G. G. Belozerskaya; V. I. Kiselev (Сибирский научный медицинский журнал, 2019)
Objective of the study is to experimentally evaluate system hemostatic and prothrombotic effects of intravenous fibrin monomer (FM). Materials and methods. Eighty two Chinchilla rabbits weighing 3–4 kg were used in the study. In addition to the placebo, animals were administered an aqueous solution of fibrin monomer (FM) intravenously at doses of 0.1, 0.25, 0.5, 1.0, 2.5 and 5.0 mg/kg. After 1 hour, a standard liver injury was performed and the blood loss (% of the circulating blood volume) resulting from parenchymal hemorrhage was estimated. Hemostatic system examination included platelet number in venous blood and fibrinogen and D-dimer levels in blood plasma. Results and discussion. Blood loss after dosed injury with placebo was 10.0 [4.0; 15.7] % blood volume (median [25th percentile; 75th percentile]). FM preparation doses of 0.25, 2.5 and 5.0 mg/kg resulted in a decrease of blood loss by 6.3 (p < 0.001), 7.8 (p < 0.001) and 2.7 times (p = 0.04) (1.6 [1.0; 3.0], 1.3 [0.6; 1,6] and 3.7 [2.8; 5.3] % blood volume, respectively).High doses of FM preparation (2.5 and 5.0 mg/kg) minimized blood loss due to activation of coagulation and thrombus formation, which was illustrated by a 7.0–8.0-fold increase in D-dimer level (compared to placebo). 0.25 mg/kg of FM preparation did not lead to an increase of D-dimer content, although the blood loss was greatly reduced. Conclusion. The data obtained show the presence of unique hemostatic properties in low-dose FM preparation (0.25 mg/kg), which allows creating system hemostatic agents of a new generation.